2022
DOI: 10.3389/fnsys.2022.837979
|View full text |Cite
|
Sign up to set email alerts
|

Event-Related Potentials as Markers of Efficacy for Combined Working Memory Training and Transcranial Direct Current Stimulation Regimens: A Proof-of-Concept Study

Abstract: Our brains are often under pressure to process a continuous flow of information in a short time, therefore facing a constantly increasing demand for cognitive resources. Recent studies have highlighted that a lasting improvement of cognitive functions may be achieved by exploiting plasticity, i.e., the brain’s ability to adapt to the ever-changing cognitive demands imposed by the environment. Transcranial direct current stimulation (tDCS), when combined with cognitive training, can promote plasticity, amplify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 126 publications
(149 reference statements)
0
7
0
Order By: Relevance
“…In all other studies, either a research assistant or study technician ( k = 4; 6%) administered the training, or it was not mentioned by whom the training was administered ( k = 61; 85%, categorized as “computerized” for the analyses). Five studies (7%) reported the use of cognitive strategies (Assecondi et al, 2022; Chapman, n.d.; Cotelli et al, 2014; Das et al, 2019; Martin et al, 2019). One study reported that the training was given in a group setting (Das et al, 2019; note that this study was one of six outliers for the cognitive outcome domain of executive functioning).…”
Section: Resultsmentioning
confidence: 99%
“…In all other studies, either a research assistant or study technician ( k = 4; 6%) administered the training, or it was not mentioned by whom the training was administered ( k = 61; 85%, categorized as “computerized” for the analyses). Five studies (7%) reported the use of cognitive strategies (Assecondi et al, 2022; Chapman, n.d.; Cotelli et al, 2014; Das et al, 2019; Martin et al, 2019). One study reported that the training was given in a group setting (Das et al, 2019; note that this study was one of six outliers for the cognitive outcome domain of executive functioning).…”
Section: Resultsmentioning
confidence: 99%
“…A recent study utilizing resting-state functional magnetic resonance imaging (fMRI) found improved brain network processing efficiency with 3-day of tDCS+WMT one day after training [40]. However, no significant effects of tDCS on brain activity were found in a 3day WMT+tDCS study that quantified long-term neurobehavioral effects using ERPs at one month [38]. Therefore, it remains an open question whether the cumulative effects of tDCS during WMT can produce lasting effects on the functional reorganization of cortical neural activity, which can be revealed by task-related EEG measures long-term after the end of training.…”
Section: Introductionmentioning
confidence: 99%
“…Pairing these types of studies with neuroscientific techniques which possess fine-grained temporal resolution like EEG and MEG, exposes unique fast-scale neural responses occurring in response to standard and discrepant stimuli (Hillebrand et al, 2018). In fact, M/EEG measurements reveal an array of contiguous automatic event-related potentials/fields (ERP/Fs) categorized into three main classes based on their latencies (Assecondi, Villa-Sánchez & Shapiro, 2022). When contextualising their succession and distinct topographies in relation to PC, it becomes evident that auditory information processing provokes spatially distributed neural responses which cross neural hierarchies at distinct processing stages.…”
Section: Introductionmentioning
confidence: 99%